PENGARUH PENURUNAN HARGA KELAPA SAWIT TERHADAP HARGA MINYAK GORENG PERKILOGRAM DI SUNGAI BANGEK TAHUN 2022 - suhaimah sitompul; Nabila Zahra Faruqi; Octavia Ningsih; Yalmi Gustian; Wafiq Azizah; Cindy Cancelia; Ikhwanul Ihsan Efendy (MAp (Mathematics and Applications) Journal, 2023)
This research was conducted in Bangek River. The purpose of this study was to determine whether there was an effect of a decrease in the price of palm oil on the price of cooking oil per kilogram in Sungai Bangek. The data that the writer uses is data obtained from interviews with cooking oil traders in Bangek River. To describe or see an overview of the object of research using descriptive statistical analysis. Cooking oil price analysis was carried out using information on the price of Fresh Fruit Bunches (FFB). To determine the relationship and influence of the independent variable (palm oil price) on the dependent variable (cooking oil price) a hypothesis test was carried out using statistical analysis with Microsoft Excel tools. Based on the results of the research and testing of the hypothesis, it can be concluded that it is true that there is an effect of a decrease in the price of palm oil on the price of cooking oil.